2011
DOI: 10.1152/jn.00339.2011
|View full text |Cite
|
Sign up to set email alerts
|

The organization of the human cerebellum estimated by intrinsic functional connectivity

Abstract: The organization of the human cerebellum estimated by intrinsic functional connectivity. J Neurophysiol 106: 2322-2345. First published July 27, 2011 doi:10.1152/jn.00339.2011The cerebral cortex communicates with the cerebellum via polysynaptic circuits. Separate regions of the cerebellum are connected to distinct cerebral areas, forming a complex topography. In this study we explored the organization of cerebrocerebellar circuits in the human using restingstate functional connectivity MRI (fcMRI). Data from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

211
2,208
7
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 4,107 publications
(2,427 citation statements)
references
References 110 publications
211
2,208
7
1
Order By: Relevance
“…13°C, 400 matm 13°C, 1100 matm 18°C, 400 matm 18°C, 1100 matm rspb.royalsocietypublishing.org Proc R Soc B 280: 20130155 pCO 2 is a strong indicator that skeletogenesis is impaired in high pCO 2 sea water and provides a mechanistic explanation for reductions in larval size at elevated pCO 2 [62]. Our results indicate that simultaneous exposure to warmer and more acidic environments can trigger metabolic depression in S. purpuratus.…”
Section: Discussionmentioning
confidence: 63%
“…13°C, 400 matm 13°C, 1100 matm 18°C, 400 matm 18°C, 1100 matm rspb.royalsocietypublishing.org Proc R Soc B 280: 20130155 pCO 2 is a strong indicator that skeletogenesis is impaired in high pCO 2 sea water and provides a mechanistic explanation for reductions in larval size at elevated pCO 2 [62]. Our results indicate that simultaneous exposure to warmer and more acidic environments can trigger metabolic depression in S. purpuratus.…”
Section: Discussionmentioning
confidence: 63%
“…This finding emerged from both Model 1 and Model 2, suggesting that this region might be the preferential regional locus of an 'O' endophenotype. The two outcome clusters overlapped with good accuracy with the cerebellar regions known to be part of a cerebro-cerebellar network responsible for sustaining sensorimotor integration (Buckner et al, 2011). Although this is not a functional circuit primarily involved in the most common forms of dementia of major aetiology (Seeley et al, 2011), a significantly smaller ABO-related GM volume in these areas might concur in fostering vulnerability for cognitive decline in old age.…”
Section: -Discussionmentioning
confidence: 88%
“…MCP mot is predominantly associated with motor‐sensory function, originates in the caudal pons and runs superior‐medially toward the anterior cerebellum. Past studies have found evidence of a rostral pons to posterior cerebellum and caudal pons to anterior cerebellum connection (Schmahmann, Rosene, & Pandya, 2004; Spitzer & Karplus, 1907; Sunderland, 1940; Von Bechterew, 1885), which is further supported by evidence that points to a caudal pons anterior lobe of cerebellum sensorimotor representation (Buckner, Krienen, Castellanos, Diaz, & Yeo, 2011; Schmahmann, MacMore, & Vangel, 2009; Schmahmann & Pandya, 1997; Schmahmann & Sherman, 1998; Stoodley & Schmahmann, 2010). The superior cerebellar peduncle pathway (SCP) consists primarily of efferent output neurons traveling from the cerebellum to higher brain centers via the mid‐brain (Hüttlova et al., 2014; Mittal et al., 2014; Ojemann et al., 2013; Schmahmann et al., 2004; Takahashi, Song, Folkerth, Grant, & Schmahmann, 2013; Von Bechterew, 1885; Wang et al., 2003).…”
Section: Introductionmentioning
confidence: 86%